Subject Access to a Data Base of Library Holdings - Clark, Alice S. (Information Technology and Libraries, 1974)
As more academic and public libraries have some form of bibliographic description of their complete collection available in machine-readable form, public service librarians are devising ways to use the information for better retrieval. Research at the Ohio State University tested user response to paper and COM output from selected areas of the shelflist. Results indicated users at remote locations found such lists helpful, with some indication that paper printout was more popular than microfiche.